PENGARUH DISIPLIN DAN STRES KERJA TERHADAP KINERJA PEGAWAI MELALUI MOTIVASI DAN KEPUASAN KERJA DI BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA KABUPATEN KARANGANYAR - Sab'atun, Tweyrianti Nuzulita (STIE AUB Surakarta)
Government agencies are required to realize good governance as the agenda of Bureaucratic Reform. In realizing good governance, it is necessary to improve performance. The purpose of this study is to examine the effect of discipline and job stress on employee performance through motivation and job satisfaction. Sampling method using survey method with respondents as much as 56 employees in Board of Human Resource Development District of Karanganyar. The data used is primary data with data collection method through questionnaire. Methods of data analysis were tested by validity test, reliability test, t test, F test, R square test and path analysis test. The result of the research proves that: discipline have negative and not significant effect to motivation, work stress have positive and significant effect to motivation, discipline have positive and significant effect to job satisfaction, work stress negatively and insignificant to job satisfaction, discipline has negative and insignificant effect to Performance, work stress have positive and insignificant effect to performance, motivation have negative and not significant to performance, job satisfaction have positive and not significant to performance. The direct influence of discipline on performance is less than indirect influence through motivational variables. The direct influence of discipline on performance is less than indirect influence through job satisfaction variables. The direct influence of job stress on performance is greater than indirect influence through motivation variables. The direct influence of job stress on performance is greater than indirect influence through job satisfaction variable. The result of F test shows that together the independent variable of discipline, work stress, work motivation, and job satisfaction have positive and significant influence to performance. The result of R2 test shows that the performance is explained by the discipline variable, job stress, motivation and job satisfaction of 31.2% and the rest 69.8% explained other variables.Keywords : Discipline, Job Stress, Motivation, Job Satisfaction, Performance